1995
DOI: 10.1111/j.1540-8191.1995.tb00619.x
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde Cerebral Perfusion with Hypothermic Blood Provides Efficient Protection of the Brain: A Neuropathological Study

Abstract: Retrograde cerebral perfusion is a method that is recently being used for protection of the brain during operations on the aortic arch. This method is useful but is said to provide a limited time for protecting the brain. We designed an experiment in dogs to investigate neuropathologically the effect of protecting the brain for 120 minutes under: (1) circulatory arrest (CA); (2) retrograde cerebral perfusion with moderately cooled blood (RCPMC); and (3) retrograde cerebral perfusion with deeply cooled blood (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The evidence for cerebral metabolic support by RCP is species dependent. Although RCP is capable of contributing to cerebral metabolism in dogs, 19 no significant cerebral blood flow or metabolic benefit has been demonstrated in baboons. 20 Evidence of true cerebral perfusion in human subjects is also limited.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence for cerebral metabolic support by RCP is species dependent. Although RCP is capable of contributing to cerebral metabolism in dogs, 19 no significant cerebral blood flow or metabolic benefit has been demonstrated in baboons. 20 Evidence of true cerebral perfusion in human subjects is also limited.…”
Section: Discussionmentioning
confidence: 99%
“…Although a metabolic effect has been seen in some species, this has not been demonstrated in man or other primates. 5,6 Other potential benefits of RCP include flushing out atheromatous or gaseous emboli and toxic metabolites, 7 and the potential maintenance of cerebral hypothermia. 8 However, RCP may also increase the risk of cerebral edema due to raised venous and intracranial pressure.…”
mentioning
confidence: 99%
“…Animal experiments also confirmed that RCP provided better cerebral protection compared with HCA alone (38,39). In addition, Imamaki et al (41) used deeply cooled blood during RCP to provide better protection of the brain. This finding suggests that enhanced cranial hypothermia, rather than brain perfusion, may be the major beneficial factor of retrograde cerebral perfusion.…”
Section: Discussionmentioning
confidence: 74%